The Economics of Natural Disasters: A Survey - Eduardo Cavallo; Ilan Noy (Inter-American Development Bank (IDB), 2009)
Catastrophes caused by natural disasters are by no means new, yet the evolving understanding of their relevance to economic development and growth is still in its infancy. In order to facilitate further necessary research on this topic, this paper summarizes the state of the economic literature examining the aggregate impact of disasters. The paper reviews the main disaster data sources available, discusses the determinants of the direct effects of disasters, and distinguishes between short- and long-run indirect effects. The paper then examines some of the relevant policy questions and follows up with projections about the likelihood of future disasters, while paying particular attention to climate change. The paper ends by identifying several significant gaps in the literature.
Keywords: O11; O40; Q54; 330; Natural disasters; Climate change; Growth